Membrane electrode assembly

By using a platinum-ruthenium catalyst to electrochemically convert hydrogen into hydrogen cations on the anode side of the PEM water electrolytic cell, the flammability or explosion problems caused by hydrogen diffusion are solved, and the efficiency of the electrolytic cell is improved.

CN119866395APending Publication Date: 2025-04-22OORT ENERGY LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202380062933.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-09-01
Filing Date
2023-08-31
Publication Date
2025-04-22

AI Technical Summary

Technical Problem

In a traditional PEM water electrolytic cell, hydrogen can diffuse through the membrane to the anode side, mix with oxygen to form a flammable or explosive gas mixture, and using a thick film to reduce hydrogen diffusion will lead to a decrease in the efficiency of the electrolytic cell.

Method used

The platinum-ruthenium (Pt-Ru) catalyst is used to be located on the anode side of the polymer electrolyte membrane, and the hydrogen is electrochemically converted into hydrogen cations to prevent the hydrogen from diffusing to the anode side. The catalyst is in electrical contact with the anode and with the membrane ions, forming a barrier to prevent hydrogen from escaping.

Benefits of technology

Effectively prevent hydrogen from diffusing from the film to the anode side, avoid mixing with oxygen to form flammable or explosive gases, and eliminate the need to use a thick film, which improves the efficiency of the electrolytic cell, especially under high voltage and high current density conditions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119866395A_ABST
    Figure CN119866395A_ABST
Patent Text Reader

Abstract

A membrane electrode assembly (MEA) for generating hydrogen gas in a water electrolyser is provided. The MEA comprises a polymer electrolyte membrane (REM); a cathode comprising a cathode catalyst on a first side of the REM; an anode comprising an anode catalyst on a second side of the REM; and a platinum-ruthenium (Pt-Ru) catalyst on a second side of the REM to electrochemically convert hydrogen to hydrogen cations in use. The Pt-Ru catalyst is in electrical contact with the anode and in contact with the REM ions.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a membrane electrode assembly (MEA for short) for a hydrogen production electrolyzer. Background Art

[0002] As the demand for renewable energy increases, there is also a growing need to produce hydrogen in a safe and efficient manner. Hydrogen is usually obtained by electrolyzing water using a water electrolyzer. A water electrolyzer is an electrochemical device that decomposes water to produce hydrogen and oxygen. Most commonly used electrolyzers have a polymer electrolyte membrane (PEM). As shown in Figure 1, a PEM water electrolyzer includes a cathode, an anode, and a polymer electrolyte. The polymer electrolyte is located between the cathode and the anode, and blocks the transfer of electrons while transferring ions between the electrodes. In addition, the catalyst is embedded in the polymer electrolyte (or surrounded by the polymer electrolyte) and is in a state below the percolation threshold to ensure the conductivity of electrons and ions. This ensures that ions can reach and leave the polymer electrolyte.

[0003] During operation of a PEM water electrolyzer, water undergoes electrochemical oxidation at the anode catalyst to generate oxygen, and hydrogen cations (protons) pass through the polymer electrolyte to the cathode catalyst where they undergo electrochemical reduction to generate hydrogen. Due to the electric field applied across the PEM, the protons migrate from the anode to the cathode. The rate of water consumption, and therefore the rate of hydrogen and oxygen production, follows Faraday's law, which states that as the current through the electrolyzer increases, the amount of gas produced and the amount of water consumed also increases accordingly. PEM electrolysis has advantages over other types of electrolysis because it produces high purity hydrogen, can produce hydrogen under pressure, and has higher efficiency than other forms of electrolysis. However, efficiency is limited by membrane resistance, especially at high current densities. Voltage loss (low efficiency) is proportional to resistance (voltage loss = current × resistance).

[0004] A problem with conventional PEM electrolyzers is that hydrogen can diffuse through the membrane to the anode side and mix with oxygen to form a flammable or explosive mixture. This is particularly true when the hydrogen is under pressure. A common solution to the hydrogen diffusion problem is to use thicker (greater than 125 μm) layers, preferably made of perfluorosulfonic acid (PSFA) polymers such as or ) membrane, which effectively reduces the diffusion of hydrogen through the membrane. However, the use of such thick membranes introduces a large ohmic resistance, which leads to a decrease in electrolyzer efficiency, especially at current densities above 1A.cm -2 hour.

[0005] Several techniques are known and have been used to minimize the accumulation of hydrogen in the anode compartment.

[0006] For example, WO 2019 / 009732 discloses a method of supplying humidified air to the anode (oxygen) chamber of a PEM electrolyser to dilute any diffused hydrogen and keep the hydrogen concentration in the atmosphere below the lower explosion limit (LEL) of the hydrogen-air mixture (approximately 4 mol%). This minimizes the risk of forming flammable or explosive gas mixtures during operation of the electrolyser. Water is applied to the cathode (hydrogen) chamber and diffuses through the membrane to the anode catalyst, where it is oxidized to protons, oxygen and electrons. However, a disadvantage of the process is that it relies on water diffusing through the membrane to the anode, which can limit current density.

[0007] M Schalenbach, D Stolten, “High pressure water electrolysis: Electrochemical mitigation of product gas crossover”, Electrochimica Acta, 156 (2015), pp. 321-327, discloses a method of embedding platinum into a PEM to prevent hydrogen diffusion. The platinum is not electrically connected to either of the two electrodes and acts as a composite catalyst, converting hydrogen and oxygen within the membrane into water. However, this method has disadvantages. Since the platinum must be embedded in the membrane, the membrane must be specially cast around the catalyst. Commercially available membranes cannot be used. Therefore, the cost of manufacturing and maintaining an electrolyzer with such an embedded catalyst is higher than that of a conventional PEM electrolyzer. In addition, since hydrogen is pressurized and oxygen is generally not, the diffusion rates of oxygen and hydrogen are different. If the diffusion rate of oxygen relative to the diffusion rate of hydrogen falls below a threshold level, the amount of hydrogen within the PEM may exceed the processing capacity of the composite catalyst, which may result in accumulation of hydrogen in the anode compartment.

[0008] The article by N. Briguglio, F. Pantò, S. Suracusano and A. Aricò, “Enhanced performance of a PtCo recombination catalyst for reducing H2 concentration in the O2 stream of a PEM electrolysis cell in the presence of a thin membrane and ahigh differential pressure”, Electrochimica Acta, 344 (2020), pp. 136153, discloses a method for using a composite catalyst (based on a platinum-cobalt alloy) located in the anode chamber to recombine hydrogen and oxygen. The disadvantage of this system is that the recombination is not very effective under humid conditions. In addition, Co has a tendency to leach out of the PtCo alloy, which limits the service life of the catalyst and can have a negative impact on the operation of the electrolyzer.

[0009] Therefore, it is necessary to develop a PEM water electrolyzer to solve the above problems at least to a certain extent. Summary of the invention

[0010] According to a first aspect of the present invention, there is provided a membrane electrode assembly (MEA) for producing hydrogen in a water electrolyser, the MEA comprising:

[0011] Polymer electrolyte membrane (PEM),

[0012] a cathode comprising a cathode catalyst on a first side of the PEM,

[0013] an anode comprising an anode catalyst on a second side of the PEM, and

[0014] a platinum-ruthenium (Pt-Ru) catalyst located on the second side of the PEM to electrochemically convert hydrogen gas into hydrogen cations in use,

[0015] The Pt-Ru catalyst is in electrical contact with the anode and in ionic contact with the PEM.

[0016] One advantage of the MEA is that it prevents hydrogen from diffusing from the PEM to the second (anode) side, particularly during high-voltage electrolysis, thereby preventing hydrogen from combining with oxygen to form flammable or explosive mixtures. Because the catalyst removes hydrogen, it eliminates the need for thick membranes used in conventional electrolyzers to limit hydrogen diffusion, and allows for thinner membranes, which improves the efficiency of the electrolyzer.

[0017] The MEA may be suitable for high pressure electrolysis, ie the production of hydrogen in a water electrolyser at a pressure of at least 30 bar.

[0018] The combination of platinum and ruthenium alloy in the catalyst has advantages over other hydrogen oxidation catalysts (such as platinum) because it does not oxidize at the working potential of the electrolyzer. When platinum contacts the anode catalyst (usually an iridium-based catalyst, such as iridium dioxide, etc.), the potential of the hydrogen oxidation catalyst becomes high, which may cause it to be oxidized to platinum oxide. Since metal oxides cannot electrochemically reduce hydrogen, this will cause the catalyst to deactivate. However, when ruthenium and platinum form an alloy, ruthenium reacts with platinum to keep platinum in its neutral oxidation state, thereby maintaining its electrochemical activity.

[0019] The thickness of the PEM may be 50 μm or less. For example, the thickness of the PEM may be less than 50 μm, may be 10 μm to 50 μm, 10 μm to 45 μm, 10 μm to 40 μm, 10 μm to 35 μm, or 10 μm to 25 μm.

[0020] The MEA may also include: an anode channel, which is connected to the anode fluid and is configured to conduct water to the anode and receive oxygen from the anode in use; and a cathode channel, which is connected to the cathode fluid and is configured to receive hydrogen from the cathode in use, wherein the Pt-Ru catalyst may be located between the PEM and the anode channel and is configured to reduce the amount of hydrogen entering the anode channel from the PEM in use.

[0021] Oxygen is generated at the anode catalyst and transported from the PEM via the anode channels as a product of the electrolysis process. The Pt-Ru catalyst effectively forms a barrier that prevents hydrogen from diffusing from the PEM into the anode channels to combine with oxygen to form a flammable mixture.

[0022] The Pt-Ru catalyst (i) may be dispersed in the anode, and / or (ii) may form a layer between the PEM and the anode.

[0023] Dispersing the Pt-Ru catalyst in the anode catalyst and / or forming a layer between the PEM and the anode catalyst enables the Pt-Ru catalyst to effectively act as a barrier between the PEM and the anode channel. In addition, mixing or dispersing the Pt-Ru catalyst into the anode catalyst enables both catalysts to be applied to the PEM in a single step without interfering with the existing MEA manufacturing process.

[0024] The Pt-Ru catalyst may be present in an amount of 0.005 to 0.5 mg / cm 2 , preferably 0.02 to 0.1 mg / cm 2 This corresponds to an anode catalyst loading of about 0.2 to 25 wt %, and to a narrower range, about 1 to 5 wt %. These amounts of the Pt-Ru catalyst are effective in preventing hydrogen from diffusing from the PEM into the anode channels.

[0025] Platinum may be present in the Pt-Ru catalyst in an amount of 10 to 90 wt%, 30 to 70 wt%, or about 50 wt%. Similarly, ruthenium may be present in the Pt-Ru catalyst in an amount of 90 to 10 wt%, 70 to 30 wt%, or about 50 wt%.

[0026] Amounts of platinum and ruthenium within these ranges provide optimized levels of hydrogen oxidation activity while minimizing platinum oxidation and extending catalyst life.

[0027] According to a second aspect of the present invention, there is provided a method for manufacturing the above-mentioned MEA, the method comprising:

[0028] A cathode catalyst is coated on a first side of a polymer electrolyte membrane (PEM),

[0029] coating an anode catalyst on a second side of the PEM, and

[0030] A Pt-Ru catalyst is applied to the second side of the PEM such that the Pt-Ru catalyst is in electrical contact with the anode catalyst and in ionic contact with the PEM.

[0031] The method may also include: fixing an anode channel over the anode catalyst so that the anode channel is in fluid communication with the anode catalyst; fixing a cathode channel over the cathode catalyst so that the cathode channel is in fluid communication with the cathode catalyst; and applying the Pt-Ru catalyst to the second side between the PEM and the anode channel.

[0032] The applying step may include:

[0033] (i) dispersing the Pt-Ru catalyst in a fluid anode catalyst to form a mixture, and coating the mixture on the PEM; and / or

[0034] (ii) forming a layer of the Pt-Ru catalyst on the PEM before coating the anode catalyst on the second side of the PEM.

[0035] The amount of catalyst applied is 0.005 to 0.5 mg / cm 2 , preferably 0.02 to 0.1 mg / cm 2 .

[0036] Platinum may be present in the Pt-Ru catalyst in an amount of 10 to 90 wt%, 30 to 70 wt%, or 50 wt%. Similarly, ruthenium may be present in the Pt-Ru catalyst in an amount of 90 to 10 wt%, 70 to 30 wt%, or 50 wt%.

[0037] The Pt—Ru catalyst in the MEA may be mainly composed of platinum and ruthenium.

[0038] According to a third aspect of the present invention, there is provided use of the MEA as described above for producing hydrogen.

[0039] As can be appreciated by those skilled in the art, the advantages of the second and third aspects of the present invention are similar to the advantages of the first aspect of the present invention described above.

[0040] The invention will be better understood with the help of the following examples and drawings, which are given in an illustrative manner only and should not be interpreted in a limiting manner. BRIEF DESCRIPTION OF THE DRAWINGS

[0041] In the attached picture:

[0042] FIG. 1 is a cross-sectional view of a prior art MEA for producing hydrogen in a water electrolyzer, showing hydrogen permeating from the cathode side to the anode side of the MEA.

[0043] Figure 2 is a cross-sectional view of an MEA for producing hydrogen in a water electrolyzer according to the present invention, wherein diffusion of hydrogen from the PEM into the anode channel is blocked by a Pt-Ru catalyst layer.

[0044] Figure 3 yes Figure 2 Schematic diagram of MEA, showing the relative positions of the anode layer, Pt-Ru catalyst layer, PEM and cathode layer.

[0045] Figure 4 Graph showing the improvement in efficiency of an electrolyser comprising an MEA according to the invention relative to an electrolyser comprising a prior art MEA.

[0046] Figure 5 is the IV curve of the electrolytic cell, showing the use of (i) a standard with a thickness of 127 μm N115 perfluorosulfonic acid (PFSA) membrane, and (ii) a membrane according to the present disclosure comprising a Ru-Pt catalyst layer (A cm -2 ) and the electrolytic cell voltage (V).

[0047] Figure 6 The hydrogen permeation rate of a standard 127 μm thick film is shown at 10 bar, 20 bar and 30 bar hydrogen pressure differences. N115 perfluorosulfonic acid (PFSA) membrane, and (ii) a membrane according to the present disclosure containing a Ru—Pt catalyst layer. DETAILED DESCRIPTION

[0048] As used herein and in the appended claims, unless the context requires otherwise, “comprise” or variations such as “comprises”, “comprising”, etc., will be understood to imply the inclusion of a stated element or group of elements but not the exclusion of any other elements or groups of elements.

[0049] As used herein, with respect to amounts expressed as a percentage by weight, the term "about" means that the stated amount can fluctuate within a range of ±10%. For example, "about 90 wt %" means 90 ± 9 wt %, and "about 0.1 wt %" means 0.1 ± 0.01 wt %. When the term "about" is used to describe a range, it applies to all values ​​within the range.

[0050] As used herein, the term "consisting essentially of," with respect to the ingredients of a composition, alloy, or mixture, means that the composition, alloy, or mixture comprises the indicated ingredients in the specified proportions, and may contain minor amounts of additional ingredients, less than 1 wt %, relative to the total weight of the composition, alloy, or mixture, provided that such additional ingredients do not materially alter the reactivity of the composition, alloy, or mixture.

[0051] In a first aspect, the present disclosure provides a membrane electrode assembly (MEA) for producing hydrogen in a water electrolyzer (electrochemical hydrogen production device), particularly under high pressure. High pressure electrolysis is usually carried out at a pressure greater than about 30 bar (e.g., 30 bar to 200 bar, 50 bar to 200 bar, 75 bar to 200 bar, or even higher than 200 bar, etc.). Figure 2 and Figure 3In the illustrated embodiment, the MEA (10) includes: a polymer electrolyte membrane (PEM) (12); a cathode (14) including a cathode catalyst (also known as a hydrogen evolution catalyst) on a first side (16) of the PEM (12); an anode (18) including an anode catalyst (also known as an oxygen evolution catalyst) on a second side (20) of the PEM (12); and a platinum-ruthenium (Pt-Ru) catalyst (22) (also known as a hydrogen oxidation catalyst) located on the second side (20) of the PEM (12). When the MEA (10) is used, the Pt-Ru catalyst (22) is suitable for electrochemically converting hydrogen gas into hydrogen cations. The Pt-Ru catalyst (22) is in electrical contact with the anode (18) and is operable to receive electrical energy for the electrochemical reaction through the anode. The Pt-Ru catalyst (22) is in ionic contact with the PEM (12) so that the hydrogen cations produced in the reaction can migrate to the cathode (14), where the hydrogen cations can be converted into hydrogen gas.

[0052] The Pt-Ru catalyst (22) provides a barrier to prevent hydrogen from escaping from the second (anode) side (20) of the PEM (12). This is particularly important when hydrogen is produced on the first (cathode) side (16) at high pressures because high pressures may increase the rate at which hydrogen diffuses through the membrane to the anode side (20). By preventing hydrogen from penetrating the membrane during high pressure electrolysis, thinner PEMs can be used without the risk of hydrogen mixing with oxygen in the anode compartment and producing a flammable or explosive mixture. The possibility of using thinner membranes during high pressure electrolysis is desirable because it improves efficiency.

[0053] The MEA (10) may also include an anode channel (24) that is in fluid communication with the anode (18) on the second side (20) of the PEM (12). The anode channel (24) may be configured to direct water for the electrolysis reaction to the anode (18) and to receive oxygen generated by the anode (18) during the water electrolysis process. In this way, the anode channel (24) may serve as a conduit through which water (liquid and / or steam) and oxygen are transported to or from the anode (18) catalyst surface. Similarly, the MEA (10) may also include a cathode channel (26) that is in fluid communication with the cathode (14) on the first side (16) of the PEM (12). The cathode channel (26) may be configured to receive hydrogen generated at the cathode (14) by water electrolysis during use and to transport the hydrogen to a storage container. The Pt-Ru alloy catalyst (22) may be located between the PEM (12) and the anode channels (24) on the second side and may be configured to reduce the amount of hydrogen entering the anode channels (24) from the PEM (12) in use.

[0054] The Pt-Ru catalyst (22) may be dispersed in the anode (18) and / or may form a layer between the PEM (12) and the anode (18). In a preferred embodiment, the Pt-Ru catalyst (22) may be simply dispersed in a solution or slurry of the anode (18) catalyst and the dispersion may then be applied to the PEM (12) using any of a variety of conventional methods known in the art (e.g., spraying, printing, etc.). In another embodiment, the Pt-Ru catalyst (22) may be coated on the anode side (20) of the PEM (12) before the anode (18) catalyst is applied to the membrane (12). Alternatively, the Pt-Ru catalyst (22) may be applied to a completed (three-layer) MEA on top of the anode catalyst. The only prerequisite is that the Pt-Ru catalyst (22) is in electrical and ionic contact with the anode catalyst and the PEM, respectively. The MEA may also include an anode diffusion layer (28) (also referred to as an anode porous transport layer) located between the anode (18) and the anode channel (24), and a cathode diffusion layer (30) (also referred to as a cathode porous transport layer) located between the cathode (14) and the cathode channel (26).

[0055] The Pt-Ru catalyst (22) may be present in the MEA (10) in an amount of about 0.001 to 1 mg / cm 2 , about 0.005 to 0.5 mg / cm 2 , about 0.01 to 0.3 mg / cm 2 or about 0.02 to 0.1 mg / cm 2 This may correspond to about 0.05 to 50 wt %, about 0.25 to 25 wt %, about 0.5 to 15 wt % or about 1 to 5 wt % of the anode catalyst loading, respectively.

[0056] The amount of platinum present in the Pt-Ru catalyst (22) can be about 10 to 90wt%, about 20 to 80wt%, about 30 to 70wt%, about 40 to 60wt%, or about 50wt%. Similarly, the amount of ruthenium present in the Pt-Ru catalyst can be about 90 to 10wt%, about 80 to 20wt%, about 70 to 30wt%, about 60 to 40wt%, or about 50wt%. Preferably, the amount of platinum and ruthenium present in the Pt-Ru catalyst is about 50wt% each. The Pt-Ru alloy catalyst (22) is mainly composed of platinum and ruthenium.

[0057] like Figure 4As shown, a water electrolyzer with a PEM having a thickness of more than 125 μm in the prior art operates at a stack efficiency (higher heating value (HHV)) of about 65 to 70%. Using a membrane having a thickness of about 50 μm, an electrolyzer containing an MEA of the present invention can operate at an efficiency of about 82% at high current density and high pressure without accumulating hydrogen in the anode channel. If a thinner membrane is used, the efficiency improvement can be even higher. For example, the MEA of the present disclosure can include a membrane having a thickness of 50 μm or less, 45 μm or less, 40 μm or less, 35 μm or less, 30 μm or less, or 25 μm or less. The thickness of the membrane can be 10 μm to 75 μm, 10 μm to 50 μm, 10 μm to 45 μm, 10 μm to 40 μm, 10 μm to 35 μm, or 10 μm to 25 μm.

[0058] In a second aspect, the present disclosure provides a method for manufacturing the above-mentioned MEA. The method comprises: coating a cathode catalyst on a first side of a polymer electrolyte membrane (PEM) to form a cathode; coating an anode catalyst on a second side of the PEM to form an anode; and applying a Pt-Ru catalyst to the second side of the PEM so that the Pt-Ru catalyst is in electrical contact with the anode catalyst and in ionic contact with the PEM.

[0059] The method may also include: fixing the anode channel above the anode catalyst so that the anode channel is in fluid communication with the anode catalyst; fixing the cathode channel above the cathode catalyst so that the cathode channel is in fluid communication with the cathode catalyst, and applying the Pt-Ru catalyst to the second side between the PEM and the anode channel. The anode channel and the cathode channel may be fixed by conventional methods known in the art. As described above, the Pt-Ru catalyst may be applied to the second side of the PEM by dispersing the Pt-Ru catalyst in a fluid anode catalyst (e.g., a solution or slurry of the anode catalyst) to prepare a mixture, and then coating the mixture on the PEM. Alternatively or additionally, the Pt-Ru catalyst may be applied to the PEM before coating the second side of the PEM with the anode catalyst, so that the Pt-Ru catalyst forms a layer between the PEM and the anode catalyst. The Pt-Ru catalyst may be applied to the PEM using conventional methods (such as spraying or printing, etc.). However, no matter which method is used, the Pt-Ru catalyst must be in electrical contact with the anode and in ionic contact with the PEM.

[0060] The catalyst may be applied to the PEM in the amounts specified above for the MEA.

[0061] Platinum and ruthenium may be present in the Pt-Ru catalyst in the amounts specified in the above MEA.

[0062] The present disclosure provides, in a third aspect, the use of the above-mentioned MEA for producing hydrogen. This use generally involves providing a water electrolyzer containing the MEA, applying electrical energy to the electrolyzer, supplying water to the electrolyzer, and collecting the hydrogen produced on the cathode side of the electrolyzer. The oxygen produced on the anode side can be discharged or collected. The hydrogen can be collected in a storage container for later use.

[0063] The invention will now be described in further detail with reference to the following non-limiting examples.

[0064] Example

[0065] Example 1:

[0066] 0.25 mg of platinum black was placed on a glassy carbon electrode with a diameter of 0.5 mm. The solution used was prepared from an ion polymer (dispersed ) and a catalyst in a ratio of 1:4 water / isopropyl alcohol (IPA) solution. The electrode was rotated at 1600 rpm using a standard turntable apparatus, and the potential was scanned from -0.05 V to 1.4 V (relative to the standard hydrogen electrode (SHE)) at a rate of 0.01 V / s while hydrogen bubbles were continuously generated from the electrode surface. The current initially rose to 2.3 A / cm 2 The current remains stable until the voltage reaches 0.97V, where it begins to drop to zero.

[0067] Note: Platinum will oxidize hydrogen, but the formation of platinum oxide will inhibit the oxidation of platinum.

[0068] Example 2:

[0069] 0.25 mg of platinum / ruthenium black in a ratio of 1:1 was placed on a glassy carbon electrode with a diameter of 0.5 mm. The solution used was prepared from an ionic polymer (dispersed The electrode was prepared by mixing a water / isopropyl alcohol (IPA) solution with a ratio of 1:4 of ) and a catalyst. The electrode was rotated at 1600 rpm using a standard turntable device, and the potential was scanned from -0.05 V to 1.4 V (relative to the standard hydrogen electrode (SHE)) at a rate of 0.01 V / s while hydrogen bubbles were continuously generated on the electrode surface.

[0070] The current initially rises to 1.4A / cm 2 The current remained stable until the voltage reached 0.97 V, when it began to drop slightly to 0.7 A / cm 2 This decrease is due to the oxidation of part of the unalloyed Pt / Ru, but the remainder continues to oxidize the hydrogen.

[0071] Example 3:

[0072] An MEA was prepared by spraying a suspension of Pt / C (platinum / carbon) and ionomer (1:1 carbon to ionomer ratio) on one side of the membrane. On the other side of the membrane, a thin layer of 1:1 platinum / ruthenium black (1:4 ionomer to catalyst ratio in the suspension) was sprayed. On top of this thin layer, another layer of iridium oxide (1:4 ionomer to catalyst ratio in the suspension) was sprayed onto the membrane. The membrane electrode assembly (MEA) was hot pressed at 140°C for 1 minute. The MEA was then placed in an electrolyzer and current was passed until a pressure difference of 5 bar was established across the membrane. While the current continued to be passed, hydrogen in the oxygen stream was monitored using a calibrated Hyoptima 720B online hydrogen process analyzer connected to a digital voltmeter DVM. The experiment was run for more than 1 hour and no hydrogen was detected in the oxygen stream (i.e., the amount of hydrogen was not above the detection level of the instrument).

[0073] Example 4:

[0074] A membrane electrode assembly (MEA) was prepared according to the method of Example 3, but without the platinum ruthenium layer. The MEA was placed in the same electrolyzer as in Example 3 and the same conditions were repeated. After 1 hour, the Hyoptima 720B online hydrogen process analyzer showed the presence of 0.7% hydrogen in oxygen.

[0075] Example 5:

[0076] The membrane electrode assembly (MEA) prepared according to the present invention (membrane coated with Oort catalyst) and the membrane electrode assembly (MEA) comprising a 127 μm thick The cell voltage and current density of MEAs with N115 perfluorosulfonic acid (PFSA) membrane were compared. The preparation methods of these two membrane electrode assemblies are as follows.

[0077] Catalyst ink is made by The ionomer suspension, catalyst and solvent (isopropanol / water mixture) were mixed and dispersed in a low-intensity ball mill. The catalyst was sprayed onto the heated vacuum plate using a commercial ultrasonic sprayer. 212 (thickness 50 μm). The platinum loading of the cathode catalyst is 0.4 mg / cm 2 The loading amount of Pt-Ru catalyst is 0.2 mg / cm 2 The loading amount of iridium oxide anode catalyst is 2.0 mg / cm 2 For the control sample, the same loading of iridium oxide anode catalyst and platinum cathode catalyst was used. The same ink was used but it was sprayed onto 115 (thickness is 125μm).

[0078] The MEA was placed in a high-voltage electrochemical cell (active area 10 cm 2 ) and apply pressure to the catalyst layer to ensure good contact (10 bar above the operating pressure). Water heated to 60°C was pumped around the oxygen chamber at a flow rate of 100 ml / min. The maximum current was applied for 1 hour to ensure stability, and then the voltage was recorded. The current was reduced and kept constant for 1 minute. The voltage was recorded after 1 minute. This process was repeated to obtain the voltage at all current densities. The results are shown in Table 1 below and are Figure 5 Shown in. Table 1

[0079] Example 6:

[0080] In order to determine the extent of hydrogen permeation through the membrane, hydrogen concentration measurements were performed in the anode chamber of the MEA of Example 5 under three different hydrogen pressure differential conditions (10 bar, 20 bar and 30 bar).

[0081] The MEA was placed in a high-voltage electrochemical cell (active area 10 cm 2 ) and pressure was applied to the catalyst layer to ensure good contact (10 bar higher than the operating pressure). Water was heated to 60°C and then pumped around the oxygen chamber at a flow rate of 100 ml / min. During the crossover measurement, the electrolyzer was operated at 1 amp.cm 2 A calibrated Hyoptima 720B (with a limit of detection (LoD) of approximately 0.4%) was placed in the oxygen waste separator tank and the device was connected to a calibrated digital voltmeter to display the hydrogen content in oxygen.

[0082] The results are shown in Table 2 below and in Figure 6 Shown in. Table 2

Claims

1. A membrane electrode assembly (MEA) for producing hydrogen in a water electrolyzer, the MEA comprising: Polymer electrolyte membrane (PEM), a cathode comprising a cathode catalyst on a first side of the PEM, an anode comprising an anode catalyst on a second side of the PEM, and a platinum-ruthenium (Pt-Ru) catalyst located on the second side of the PEM to electrochemically convert hydrogen gas into hydrogen cations in use, The Pt-Ru catalyst is in electrical contact with the anode and in ionic contact with the PEM.

2. The MEA according to claim 1, further comprising: an anode channel in fluid communication with the anode and configured, in use, to direct water to the anode and receive oxygen from the anode; as well as A cathode channel is in fluid communication with the cathode and is configured to receive hydrogen from the cathode in use, wherein a Pt-Ru alloy catalyst is located between the PEM and the anode channel and is configured to reduce the amount of hydrogen entering the anode channel from the PEM in use.

3. The MEA according to claim 1 or 2, wherein: The MEA is suitable for producing hydrogen in a water electrolyser at a pressure of at least 30 bar.

4. The MEA according to any one of claims 1 to 3, wherein The thickness of the PEM is 50 μm or less.

5. The MEA according to any one of claims 1 to 4, wherein The Pt-Ru catalyst: (i) dispersed in the anode; and / or (ii) forming a layer between the PEM and the anode.

6. The MEA according to any one of claims 1 to 5, wherein: The Pt-Ru catalyst is present in an amount of 0.005 to 0.5 mg / cm 2 , preferably 0.02 to 0.1 mg / cm 2 .

7. The MEA according to any one of claims 1 to 6, wherein: Platinum is present in the Pt—Ru catalyst in an amount of 10 to 90 wt %, 30 to 70 wt %, or 50 wt %.

8. The MEA according to any one of claims 1 to 7, wherein Ruthenium is present in the Pt—Ru catalyst in an amount of 90 to 10 wt %, 70 to 30 wt %, or 50 wt %.

9. A method for manufacturing an MEA according to any one of claims 1 to 8, comprising: A cathode catalyst is coated on a first side of a polymer electrolyte membrane (PEM), coating an anode catalyst on a second side of the PEM, and A Pt-Ru catalyst is applied to the second side of the PEM such that the Pt-Ru catalyst is in electrical contact with the anode catalyst and in ionic contact with the PEM.

10. The method according to claim 9, further comprising: fixing an anode channel over the anode catalyst so that the anode channel is in fluid communication with the anode catalyst, securing a cathode channel over the cathode catalyst such that the cathode channel is in fluid communication with the cathode catalyst, and The Pt-Ru catalyst is applied to the second side between the PEM and the anode channel.

11. The method according to claim 9 or 10, wherein: The applying step comprises: (i) dispersing the Pt-Ru catalyst in a fluid anode catalyst to form a mixture, and coating the mixture on the PEM; and / or (ii) forming a layer of the Pt-Ru catalyst on the PEM before coating the second side of the PEM with the anode catalyst.

12. The method according to any one of claims 9 to 11, wherein: The amount of the catalyst applied is 0.005 to 0.5 mg / cm 2 , preferably 0.02 to 0.1 mg / cm 2 .

13. The method according to any one of claims 9 to 12, wherein: Platinum is present in the Pt—Ru catalyst in an amount of 10 to 90 wt %, 30 to 70 wt %, or 50 wt %.

14. The method according to any one of claims 9 to 13, wherein: Ruthenium is present in the Pt—Ru catalyst in an amount of 90 to 10 wt %, 70 to 30 wt %, or 50 wt %.

15. Use of the MEA according to any one of claims 1 to 8 for producing hydrogen.

Citation Information

Patent Citations

  • A method for producing hydrogen in a PEM water electrolyser system, PEM water electrolyser cell, stack and system

    WO2019009732A2